The X‐ray crystallography phase problem solved thanks to AlphaFold and RoseTTAFold models: a case‐study report. Corrigendum. Issue 4 (30th March 2023) - Barbarin-Bocahu, Irène; Graille, Marc
Abstract : The article by Barbarin‐Bocahu & Graille [(2022), Acta Cryst. D78, 517–531] is corrected. Abstract : A figure in the article by Barbarin‐Bocahu & Graille [(2022), Acta Cryst. D78, 517–531] is corrected.